Anthrax outbreak: exploring its biological agents and public health implications - Ogunleye, Seto C.; Olorunshola, Mercy M.; Fasina, Kolapo A.; Aborode, Abdullahi T.; Akinsulie, Olalekan C.; Amoo, Abimbola; Olatoye, Boluwatife J.; Bakare, Akeem; Lawal, Mariam A.; Adekanye, Oluwabori; Chinyere, Ezemba C. (Frontiers in Tropical Diseases, 2024)
The (re)emergence of several infectious zoonoses underlines the need for a re-evaluation of the transmission patterns and key players responsible for effective inter-species transfer of diseases. Anthrax is caused by Bacillus anthracis (B. anthracis), a zoonotic rod shaped gram-positive, spore-forming, zoonotic bacterium that is highly fatal in both human and animal populations. The widespread of B. anthracis across several nations of the world including Africa, Asia, South Europe, North and South America, and Australia with attendant significant impact on the livestock's sustainability and profitability is remarkable. The current trend in global distribution of anthrax necessitates an urgent contextual understanding of the key drivers of the spread of B. anthracis in different parts of the world towards the end goal of an anthrax-free world. The understanding of the drivers is integral for development of control and preventive measures, as well as development of agents such as therapeutics and vaccines against B. anthracis. This review presents a holistic description of the transmission pattern and epidemiology of the B. anthracis, updates on diagnostic techniques and approaches, and highlights plausible prevention and control strategies. This review further underscores the need for participatory epidemiology, hygienic and safety protocols, the establishment of comprehensive surveillance systems and global collaborative efforts toward vaccine development as critical steps in controlling anthrax.